2010
DOI: 10.1097/cji.0b013e3181fb0486
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Inhibits T-cell Proliferation While Preserving the Cytolytic Function of EBV, CMV, and MART-1-specific CTLs

Abstract: Statin treatment has been shown to reduce graft-versus-host disease (GVHD) while preserving graft-versus-tumor (GVT) effect in allogeneic stem cell transplantation (allo-HCT). Herein, we investigated whether lovastatin treatment affects the function of human cytolytic T lymphocytes (CTLs). Upon TCR stimulation, lovastatin significantly inhibited the proliferation of both CD4+ and CD8+ T cells from healthy donors while their intracellular cytokine production including IFN-γ and TNF-α remained the same with a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Consistently, the number of these inflammatory and immune response cells was remarkably reduced in DVT animals after rosuvastatin treatment. Our findings are consistent with those of previous studies [23,24].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Consistently, the number of these inflammatory and immune response cells was remarkably reduced in DVT animals after rosuvastatin treatment. Our findings are consistent with those of previous studies [23,24].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, statin has been suggested to shed some light on the pathogenesis of immunosuppressive graftversus-host disease [23,24]. An essential finding in the present study is that the number of immune response cells (CD3+/CD4+ helper T cells, CD3+/CD8+ cytotoxic T cells and CD4 + CD25 + Foxp3+ Tregs) were markedly increased in DVT animals compared with that in SC animals by days 2, 6 and 14 after IVC-stenosis procedure.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Drugs such as lovastatin have been used to lower cell cholesterol levels in virus-infected cells (39)(40)(41) by affecting intermediate steps in the cholesterol-biosynthetic pathway but function only after several hours. The HSV-1 replicative cycle is complete within 18 to 24 h, and the rapid action of M␤CD in reducing cell cholesterol was better suited to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [8] have observed that fluvastatin inhibited proliferation of hepatocellular carcinoma cell lines (HepG2, SMMC-7721 and MHCC-97H) by inducing apoptosis and G2/M phase arrest in a dose-dependent manner. In another experiment, acquired data demonstrated that lovastatin inhibits the proliferation of MART-1-specific human cytolytic T lymphocytes without affecting cytolytic capacity [19]. In the study of Bessler et al [20] malignant cell lines -HuCC, EHEB, K562, and Raji were incubated with three lipophilic statins (atorvastatin, lovastatin, and simvastatin) and one hydrophilic statin (pravastatin).…”
Section: Discussionmentioning
confidence: 99%